Nengsemaken in Surakarta Karaton Karawitan Performance - Joko Daryanto (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2019)
The Surakarta Karaton Karawitan which has lived and developed for centuries in the Javanese culture and its distribution leaves many questions, especially those related to the aesthetic concept of the Surakarta Karaton karawitan. The description of the Surakarta Karaton Karawitan musical concept as a reference for the Surakarta community has not been widely revealed. This article aims to reveal and describe one of the aesthetic concepts of the Surakarta Karaton Karawitan, namely the concept of nengsemaken. The paradigm of text and context is used to see the Surakarta Karaton Karawitan events as readable sentences or texts. Texts or sentences have tendency with certain meanings that show certain thoughts that ultimately produce meaning. The concept of interpretation of Clifford Geertz was used to read and interpret musical events in the Surakarta Karaton. From the study conducted, nengsemaken was interpreted as tan sora swarané, rempek rampak kabèh mung jinawil, and sajanturing ringgit.